Present and Importance levels leadership competencies of principals in Nepalese Schools - Thapa, Karna Bahadur (Journal of Advanced Academic Research, 2017)
Leadership competency is one of the major qualities of Principal to ensure the performance of schools. Principal is responsible to manage the overall school's environment so that s/he should have effective leadership competency. The study was explored the present level and desired level of leadership competency of principal of Nepalese schools. The study had applied Stratified proportionate sampling to select the 817 respondents from Principal, Teachers and Supervisor. The secondary level schools - government aided, community managed and institutional were selected from the Tarai, Mountain, Hill and Valley. The study found that there was significant difference between the present level and Importance level of leadership competency of Principals of Nepalese schools. The statistical analysis of t-test showed that the mean value of Importance level of competency was significantly higher than the mean value of present level of competency on the basis of types of schools and types of respondents. The study observed that there was need of improvement in present level of leadership competency of principals.